The principal components of the career prospects of senior schoolchildren - Anna V. Kurilova; Aleksandr L. Enin (Rossijskij psihologičeskij žurnal., 2018)
The paper brings forward the results of the scientific study of senior schoolchildren’s (at the stage of graduation from secondary school) representations of their career prospects. The study of features of senior schoolchildren’s career planning is the urgent problem of scientific studying. The authors (a) suggested understanding career prospects from the point of view of the system approach, (b) described the structure and designated the components of career prospects in senior schoolchildren. Being based on fundamental provisions of the system approach and the content of the “life prospects” definition, the authors distinguished principal structural components of career prospects: cognitive, affective, motivational, value, and behavioral. The paper presents a model of career prospects; the degree of the formation of components of this model was the main criterion for determining its development/presence. The analysis of the respondents’ representations of their career prospects enabled authors to distinguish four basic types of career prospects: fully formed, partially formed, insufficiently formed, and unformed ones. The analysis of the results of the empirical study made it possible to quantitatively and qualitatively describe the features of the components of career prospects in senior schoolchildren at the stage of graduation from secondary school. The duration of senior schoolchildren’s individual planning of career prospects manifested itself in three stages: the stage of nearest career prospects (from three months to six months), stage of medium career prospects (from three to five years), and the stage of distant career prospects (from five to ten years). The results of the study showed the following principal factors of career prospects in the group of senior schoolchildren: “concrete life values”, “social activity to achieve status”, “altruism”, “need for  communication”.